AN ANALYTICAL STUDY OF THE PROGRAM "LEGAL ISSUES" ON ALIRAQIYA SATELLITE CHANNEL - Muhsen, Haider Ali Abd AlSahib (Journal of Social Science, 2025)
Objective: This study aims to answer a set of research questions, which can be stated as follows: What proportion of airtime does the program Legal Issues occupy compared to the total airtime of other programs on AlIraqiya Satellite Channel? What are the prominent legal topics that the program seeks to present and emphasize within the episodes aired? What are the main goals and functions the program aims to achieve through its presented topics, ideas, and legal issues? Method: This research is classified as a descriptive study, aiming to determine the scope of topics and functions performed by the Legal Issues television program. The study covers the period from June 1, 2024, to August 30, 2024, during which the recorded episodes of Legal Issues were aired, constituting one complete programming cycle. The researcher selected this period because it coincided with the study timeline, which allowed close monitoring of the Legal Issues program broadcast on AlIraqiya Satellite Channel. Results: Legal topics hold particular significance for the public as they contribute to building the audience’s knowledge base after becoming familiar with the enacted laws and regulations. By presenting legal topics through mass media, public awareness is enhanced, and individuals are provided with the skill of logical legal thinking, considering that such topics are important and complementary to social, political, and literary subjects. Novelty: The scientific problem addressed in this research lies in the fact that television seeks to perform and fulfil several functions, with the legal function being one of its key aspects. Therefore, television professionals strive to leverage its ability to influence, guide, and educate in order to achieve culturally and socially beneficial objectives in general, and legal objectives in particular, aimed at raising legal awareness and informing the public of their rights and obligations within the framework of prevailing legal systems.